Development of morbidity and mortality of SARS-CoV-2 in nursing homes for the elderly in Frankfurt am Main, Germany, 2020-2022: What protective measures are still required? - Heudorf, Ursel; Domann, Eugen; Förner, Markus; Kunz, Sabine; Latasch, Leo; Trost, Bernd; Steul, Katrin (German Medical Science GMS Publishing House, 2023)
Introduction: Nursing-home residents are among the highest risk group in the SARS-CoV-2 pandemic. At the onset of the SARS-CoV-2 pandemic, the majority of all deaths from or with SARS-CoV-2 occurred in long-term care facilities (LTCFs), so that maximum protective measures were mandated for these facilities. This study analyzed the impact of the new virus variants and the vaccination campaign on disease severity and mortality among nursing home residents and staff through 2022 as a basis for determining which protective measures remain necessary and appropriate. Methods: In five homes in Frankfurt am Main, Germany, with a total capacity for 705 residents, all cases occurring in the facility among residents and staff were recorded and documented (date of birth and diagnosis, hospitalization and death, vaccination status) and were descriptively analyzed with SPSS.Results: By 31 August 2022, 496 residents tested positive for SARS-CoV-2, 93 in 2020, 136 in 2021, and 267 in 2022; 14 residents presented with a second SARS-CoV-2 infection in 2022, having previously experienced an infection in 2020 or 2021. The percentage of hospitalizations decreased from 24.7% (2020) and 17.6% (2021) to 7.5% (2022), and the percentage of deaths decreased from 20.4% and 19.1% to 1.5%. In 2021, 61.8% of those infected were vaccinated (at least 2x); in 2022, 86.2% of residents had been vaccinated twice, 84% of whom had already had a booster vaccination. Hospitalization and death rates were significantly higher among the unvaccinated than the vaccinated throughout all years (unvaccinated 21.5% and 18.0%; vaccinated 9.8% and 5.5%; KW test p=0.000). However, this difference was no longer significant under the prevalence of the Omicron variant in 2022 (unvaccinated 8.3% and 0%; p=0.561; vaccinated 7.4% and 1.7%; p=0.604). From 2020 to 2022, 400 employees were documented as infected, with 25 having second infections in 2022. Only one employee showed a second infection in 2021 following the first in 2020. Three employees were hospitalized; no deaths occurred. Discussion and conclusion: Severe COVID-19 courses occurred with the Wuhan Wild type in 2020, with a high death rate among nursing-home residents. In contrast, during the waves in 2022 with the relatively mildly pathogenic Omicron variant, many infections but few severe courses and deaths were observed among the now mostly vaccinated and boostered nursing-home residents. Given the high immunity of the population and the low pathogenicity of the circulating virus - even in nursing-home residents - protective measures in nursing homes that restrict people's right to self-determination and quality of life no longer seem justified. Instead, the general hygiene rules and the recommendations of the KRINKO (German Commission for Hospital Hygiene and Infection Prevention) on infection prevention should be followed, and the recommendations of the STIKO (German Standing Commission on Vaccination) on vaccination not only against SARS-CoV-2 but also against influenza and pneumococci should be observed.